Z-type hexagonal ferrite magnetoelectric coupling ceramic material and preparation method thereof
The Z-type hexagonal ferrite ceramic material with adjusted Ba and Sr ratios achieves enhanced magnetoelectric coupling, addressing the limitations of existing materials by providing strong coupling and temperature tolerance beyond room temperature, suitable for magnetoelectric coupling applications.
Patent Information
- Application Number
- CN202411415461.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-11
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-10-11
Smart Images

Figure CN119219405A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of magnetoelectric coupling materials, and in particular relates to a Z-type hexagonal ferrite magnetoelectric coupling ceramic material and a preparation method thereof. Background Art
[0002] Magnetoelectric coupling materials refer to materials whose ferroelectric polarization or magnetic state changes under the influence of external magnetic field or electric field, that is, materials whose magnetic state can be controlled by electric field or whose ferroelectric polarization can be controlled by external magnetic field. Among them, multiferroic materials have application prospects in microwave, sensor control and information storage fields, and are becoming a hot topic for scientific researchers because they have ferroelectric, ferromagnetic or ferroelastic order and magnetoelectric coupling effect.
[0003] The Chinese patent application number CN201711172802.0, "Bismuth ferrite room temperature multiferroic magnetoelectric coupling material and preparation method, electronic device", discloses a bismuth ferrite room temperature multiferroic magnetoelectric coupling material. The structural formula of the material is AB x O y , having a hexagonal crystal structure. Wherein A is one or more of Bi, Pb, Sb, Sn or rare earth metal elements, and B is one or more of transition metal elements Fe, Sc, Ti, V, Cr, Mn, Co, Ni, Zn, and Cu. The material has both ferroelectricity and ferrimagnetism with a transition temperature higher than room temperature, ferroelectricity at 800K or less, ferromagnetism or ferrimagnetism at 600K or less, and within the temperature range below 600K, the ferroelectricity and ferromagnetism or ferrimagnetism of the bismuth iron oxide room temperature multiferromagnetic electric coupling material coexist. It is prepared by heating a material containing an ABO component to generate a molecular beam, an atomic beam or a plasma and depositing it on a substrate. Summary of the invention
[0004] The present invention aims to solve the problem that there are few types of existing multiferroic materials that have both ferroelectricity and ferromagnetism, low magnetoelectric coupling strength, and low magnetoelectric coupling tolerance temperature that is difficult to break through room temperature; and to provide a Z-type hexagonal ferrite magnetoelectric coupling ceramic material and a preparation method thereof. The Z-type hexagonal ferrite magnetoelectric coupling ceramic material of the present invention has both ferroelectricity and ferromagnetism, and has a strong magnetoelectric coupling effect, while the magnetoelectric coupling tolerance temperature breaks through the room temperature limit. The Z-type hexagonal ferrite magnetoelectric coupling ceramic material of the present invention can induce the electric polarization performance of the sample under a small applied magnetic field, and the electric polarization direction of the Z-type hexagonal ferrite magnetoelectric coupling ceramic material of the present invention can be regulated by regulating the pre-polarization electric field direction and the magnetic field scanning direction. At the same time, the preparation process of the Z-type hexagonal ferrite magnetoelectric coupling ceramic material of the present invention is simple, which broadens the application of ferrite magnetoelectric coupling ceramic materials in the field of magnetoelectric coupling.
[0005] The Z-type hexagonal ferrite magnetoelectric coupling ceramic material of the present invention has both ferroelectricity and ferromagnetism, and its dynamic magnetoelectric coupling performance can be regulated by an external small magnetic field, and the dynamic magnetoelectric coupling performance of the Z-type hexagonal ferrite magnetoelectric coupling ceramic material of the present invention changes with the change of the direction of the external magnetic field. The direction of the dynamic magnetoelectric coupling performance of the Z-type hexagonal ferrite magnetoelectric coupling ceramic material can be effectively regulated by different positive and negative polarized electric fields. The dynamic magnetoelectric coupling performance induced by the external magnetic field of the Z-type hexagonal ferrite magnetoelectric coupling ceramic material of the present invention can withstand a temperature exceeding room temperature, breaking the bottleneck problem of the magnetoelectric coupling field that the magnetoelectric coupling performance can withstand a temperature at or below room temperature, and laying a solid foundation for the practical application of magnetoelectric coupling materials under environmental conditions at or above room temperature. The method adopted by the present invention is a traditional solid-phase sintering method, and the preparation process is simple, and the prepared samples are of high quality and excellent performance.
[0006] In order to solve the above technical problems, the present invention adopts the following technical solutions:
[0007] The object of the present invention is to provide a Z-type hexagonal ferrite magnetoelectric coupling ceramic material, the chemical formula of which is Ba x Sr 3-x Co 1.25 Cu 0.75 Fe 24 O 41 , wherein x=0 to 3. It is prepared according to the following steps:
[0008] Step 1: According to the chemical formula of Z-type hexagonal ferrite Ba x Sr 3-x Co 1.25 Cu 0.75 Fe 24 O 41 BaCO3, SrCO3, Co3O4, CuO and Fe2O3 are weighed in a stoichiometric ratio, and then put into a ball mill together for wet ball milling; after ball milling, they are dried, and then put into a ball mill again for dry ball milling to obtain a mixed powder;
[0009] Step 2: Put the mixed powder obtained in step 1 into an alumina crucible, then transfer it to a box furnace, heat it to 1000°C-1140°C at a rate of 5°C / min and keep it for 10 hours, then cool it to 500°C at a rate of 5°C / min and stop the sintering process; cool it naturally to room temperature to obtain pre-sintered powder;
[0010] Step 3: Place the pre-burned powder obtained in step 2 into a ball mill for wet ball milling; dry the powder after ball milling, and then place the powder into a ball mill for dry ball milling to obtain a coarse material powder;
[0011] Step 4: adding polyvinyl alcohol (PVA) solution to the crude material powder obtained in step 3, grinding evenly, sieving, and tableting to obtain a block body;
[0012] Step 5: putting the block green body obtained in step 4 into a box-type furnace, heating it to a certain temperature and keeping it for a certain time to debind, so as to obtain a debinded green body;
[0013] Step six, place the debinding body obtained in step five into a box furnace, heat the box furnace to 1000°C at a rate of 5°C / min in an air atmosphere, then heat the sample to 1100°C-1140°C at a rate of 2°C / min and maintain for 10 hours, then cool it to 1000°C at a rate of 2°C / min, then cool it to 500°C at a rate of 5°C / min, turn off the program, and then naturally cool it to room temperature to obtain Z-type hexagonal ferrite.
[0014] Step 7: Place the Z-type hexagonal ferrite obtained in step 6 into a tube furnace. In an oxygen atmosphere, heat the tube furnace to 950°C at a rate of 5°C / min and keep it warm for 14 days. Then cool it to 500°C at a rate of 5°C / min and stop the sintering process. Then naturally cool it to room temperature to obtain a Z-type hexagonal ferrite magnetoelectric coupling ceramic material.
[0015] It is further defined that the wet ball milling described in step one is to add the raw materials BaCO3, SrCO3, Co3O4, CuO and Fe2O3 into the ball milling jar of a planetary ball mill, and then add 140mL of ethanol with a mass percentage concentration of 95%, the number of small balls in the ball milling jar is about 30, and the ball milling is carried out at a speed of 400r / min for 12h.
[0016] It is further defined that the drying in step 1 is carried out in an oven at a temperature of 90° C. for 8 hours.
[0017] It is further defined that the dry ball milling described in step 1 is to add the material into a ball milling jar of a planetary ball mill, the number of balls in the ball milling jar is 30, and the ball milling is performed at a rotation speed of 500 r / min for 10 minutes.
[0018] It is further defined that in step 4, the product is sieved through a 100-mesh sieve.
[0019] It is further defined that in step 4, the sieved powder is tableted using a tablet press under a pressure of 6 MPa.
[0020] It is further defined that the mass percentage concentration of the polyvinyl alcohol (PVA) solution described in step 4 is 5%; 10 drops of 5% mass percentage concentration of polyvinyl alcohol (PVA) solution are added to 5g of crude material powder.
[0021] It is further defined that in step five, the temperature is raised to 500° C. and maintained for 10 hours for debinding.
[0022] It is further defined that in step seven, oxygen is introduced into the furnace tube of the tubular furnace at a flow rate of 100 mL / min to obtain an oxygen atmosphere.
[0023] The Z-type hexagonal ferrite magnetoelectric coupling ceramic material Ba of the present invention x Sr 3-x Co 1.25 Cu 0.75 Fe 24 O 41 (x=0~3) has good magnetoelectric coupling performance, among which when x=0.2-1.8, Ba x Sr 3-x Co 1.25 Cu 0.75 Fe 24 O 41 (x=0.2~1.8) shows the phenomenon that the dynamic magnetoelectric coupling coefficient signal response is reversed with the external sweep field under low temperature 78K, and the prepolarization electric field can effectively regulate the dynamic magnetoelectric coupling coefficient signal response of Z-type hexagonal ferrite magnetoelectric coupling ceramic material. Especially when x=0.2-1.0, Ba x Sr 3-x Co 1.25 Cu 0.75 Fe 24 O 41 (x = 0.2 ~ 1.0) still has dynamic magnetoelectric coupling response at room temperature (300K) and above, and the maximum tolerance temperature reaches 350K. x Sr 3- x Co 1.25 Cu 0.75 Fe 24 O 41 (x=0.2~1.0) At room temperature 300K, the dynamic magnetoelectric coupling coefficient signal response shows a phenomenon of reversal with the reversal of the external scanning field, and the prepolarization electric field can effectively regulate the dynamic magnetoelectric coupling coefficient signal response of the sample.
[0024] The innovation of this application is that the ratio of the element Ba and the element Sr in the Z-type hexagonal ferrite is adjusted to achieve the Z-type hexagonal ferrite magnetoelectric coupling ceramic material Ba x Sr 3-x Co 1.25 Cu 0.75 Fe 24 O 41By regulating the magnetoelectric coupling properties of (x=0~3), Z-type hexagonal ferrite magnetoelectric coupling ceramic materials with dynamic magnetoelectric coupling properties were screened and prepared. The magnetoelectric coupling performance of some Z-type hexagonal ferrite magnetoelectric coupling ceramic materials can withstand temperatures exceeding room temperature (300K), and even the highest tolerance temperature reaches 350K, which broadens the application of the material in the field of magnetoelectric coupling.
[0025] The Z-type hexagonal ferrite magnetoelectric coupling ceramic material of the present invention is prepared by a conventional solid phase sintering method, which is simple and has low requirements on equipment.
[0026] The Z-type hexagonal ferrite magnetoelectric coupling ceramic material of the present invention has both ferroelectricity and ferromagnetism and has strong magnetoelectric coupling performance. The Z-type hexagonal ferrite magnetoelectric coupling ceramic material of the present invention can induce the dynamic magnetoelectric coupling performance of the Z-type hexagonal ferrite magnetoelectric coupling ceramic material under the condition of a small external magnetic field. And the dynamic magnetoelectric coupling coefficient signal of the Z-type hexagonal ferrite magnetoelectric coupling ceramic material of the present invention can be regulated by changing the prepolarization electric field and the magnetic field scanning direction. Some Z-type hexagonal ferrite magnetoelectric coupling ceramic materials realize dynamic magnetoelectric coupling response at room temperature and above, and can be applied to the field of magnetoelectric coupling. It enriches and broadens the application scope of magnetoelectric materials and has potential application advantages.
[0027] In order to further understand the features and technical contents of the present invention, please refer to the following detailed description and drawings of the present invention. However, the attached drawings are only provided for reference and illustration and are not intended to limit the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 The Sr3Co of Examples 1 to 12 1.25 Cu 0.75 Fe 24 O 41, Ba 0.2 Sr 2.8 Co 1.25 Cu 0.75 Fe 24 O 41 , Ba 0.6 Sr 2.4 Co 1.25 Cu 0.75 Fe 24 O 41, Ba 1.0 Sr 2.0 Co 1.25 Cu 0.75 Fe 24 O 41, Ba 1.2 Sr 1.8 Co 1.25 Cu0.75 Fe 24 O 41, Ba 1.4 Sr 1.6 Co 1.25 Cu 0.75 Fe 24 O 41, Ba 1.5 Sr 1.5 Co 1.25 Cu 0.75 Fe 24 O 41, Ba 1.6 Sr 1.4 Co 1.25 Cu 0.75 Fe 24 O 41, Ba 1.8 Sr 1.2 Co 1.25 Cu 0.75 Fe 24 O 41, Ba 2.2 Sr 0.8 Co 1.25 Cu 0.75 Fe 24 O 41, Ba 2.6 Sr 0.4 Co 1.25 Cu 0.75 Fe 24 O 41, Ba3Co 1.25 Cu 0.75 Fe 24 O 41 Scanning electron microscope photos of
[0029] Figure 2 The Sr3Co of Examples 1 to 12 1.25 Cu 0.75 Fe 24 O 41, Ba 0.2 Sr 2.8 Co 1.25 Cu 0.75 Fe 24 O 41 , Ba 0.6 Sr 2.4 Co 1.25 Cu 0.75 Fe 24 O 41, Ba 1.0 Sr 2.0 Co 1.25 Cu 0.75 Fe24 O 41, Ba 1.2 Sr 1.8 Co 1.25 Cu 0.75 Fe 24 O 41, Ba 1.4 Sr 1.6 Co 1.25 Cu 0.75 Fe 24 O 41, Ba 1.5 Sr 1.5 Co 1.25 Cu 0.75 Fe 24 O 41, Ba 1.6 Sr 1.4 Co 1.25 Cu 0.75 Fe 24 O 41, Ba 1.8 Sr 1.2 Co 1.25 Cu 0.75 Fe 24 O 41, Ba 2.2 Sr 0.8 Co 1.25 Cu 0.75 Fe 24 O 41, Ba 2.6 Sr 0.4 Co 1.25 Cu 0.75 Fe 24 O 41, Ba3Co 1.25 Cu 0.75 Fe 24 O 41 XRD pattern of
[0030] Figure 3 Example 1 Sr3Co 1.25 Cu 0.75 Fe 24 O 41 The dynamic magnetoelectric coupling performance induced by the magnetic field under positive and negative polarization electric field conditions.
[0031] Figure 4 Example 2Ba 0.2 Sr 2.8 Co 1.25 Cu 0.75 Fe 24 O 41The dynamic magnetoelectric coupling performance induced by the magnetic field under positive and negative polarization electric field conditions.
[0032] Figure 5 Example 3Ba 0.6 Sr 2.4 Co 1.25 Cu 0.75 Fe 24 O 41 The dynamic magnetoelectric coupling performance induced by the magnetic field under positive and negative polarization electric field conditions.
[0033] Figure 6 Example 4Ba 1.0 Sr 2.0 Co 1.25 Cu 0.75 Fe 24 O 41 The dynamic magnetoelectric coupling performance induced by the magnetic field under positive and negative polarization electric field conditions.
[0034] Figure 7 Example 5Ba 1.2 Sr 1.8 Co 1.25 Cu 0.75 Fe 24 O 41 The dynamic magnetoelectric coupling performance induced by the magnetic field under positive and negative polarization electric field conditions.
[0035] Figure 8 Example 6Ba 1.4 Sr 1.6 Co 1.25 Cu 0.75 Fe 24 O 41 The dynamic magnetoelectric coupling performance induced by the magnetic field under positive and negative polarization electric field conditions.
[0036] Fig. 9 Example 7Ba 1.5 Sr 1.5 Co 1.25 Cu 0.75 Fe 24 O 41 The dynamic magnetoelectric coupling performance induced by the magnetic field under positive and negative polarization electric field conditions.
[0037] Fig.10 Example 8Ba 1.6 Sr 1.4 Co 1.25 Cu 0.75 Fe 24 O 41 The dynamic magnetoelectric coupling performance induced by the magnetic field under positive and negative polarization electric field conditions.
[0038] Fig.11 Embodiment 9Ba 1.8 Sr 1.2 Co 1.25 Cu 0.75 Fe 24 O 41 The dynamic magnetoelectric coupling performance induced by the magnetic field under positive and negative polarization electric field conditions.
[0039] Fig.12 Example 10Ba 2.2 Sr 0.8 Co 1.25 Cu 0.75 Fe 24 O 41 The dynamic magnetoelectric coupling performance induced by the magnetic field under positive and negative polarization electric field conditions.
[0040] Fig.13 Example 11Ba 2.6 Sr 0.4 Co 1.25 Cu 0.75 Fe 24 O 41 The dynamic magnetoelectric coupling performance induced by the magnetic field under positive and negative polarization electric field conditions.
[0041] Fig.14 Example 12Ba3Co 1.25 Cu 0.75 Fe 24 O 41 The dynamic magnetoelectric coupling performance induced by the magnetic field under positive and negative polarization electric field conditions. DETAILED DESCRIPTION
[0042] The present invention will be described in detail below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, and do not limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present invention. These all fall within the scope of protection of the present invention.
[0043] Example 1: The chemical formula of the Z-type hexagonal ferrite magnetoelectric coupling ceramic material of this example is Sr3Co 1.25 Cu 0.75 Fe 24 O 41 , is prepared according to the following steps:
[0044] Step 1: Press Z-type hexagonal ferrite Sr3Co 1.25 Cu 0.75 Fe 24 O41 0 g BaCO3, 6.6433 g SrCO3, 1.5049 g Co3O4, 0.9155 g CuO and 28.7438 g Fe2O3 were weighed in a stoichiometric ratio, and then put into a ball mill, and then 140 mL of 95% ethanol was added, and the mixture was ball milled at a speed of 400 r / min for 12 h; after the ball milling was completed, the mixture was placed in an oven at a temperature of 90°C for 4 hours for drying, and then placed in a ball mill and ball milled at a speed of 500 r / min for 10 min, the number of balls in the ball mill was about 30, and a mixed powder was obtained;
[0045] Step 2: Put the mixed powder obtained in step 1 into an alumina crucible, transfer it to a box furnace, heat it to 1000°C at a rate of 5°C / min and keep it for 10 hours, then cool it to 500°C at a rate of 5°C / min and then close the program; cool it naturally to room temperature to obtain pre-sintered powder;
[0046] Step 3: put the calcined powder obtained in step 2 into a ball mill, add 140 mL of 95% ethanol by mass, and mill at a speed of 400 r / min for 12 hours; after the ball milling is completed, place it in an oven at a temperature of 90° C. for 8 hours to dry, and then put it into a ball mill again after drying. The number of balls in the ball mill is about 30, and the ball mill is milled at a speed of 500 r / min for 10 minutes to obtain a coarse material powder;
[0047] Step 4: add 10 drops of 5% polyvinyl alcohol (PVA) solution to 5 g of the crude material powder obtained in step 3, grind in an agate mortar for 1 h, then pass through a 100-mesh sieve, and use a tablet press to press the sieved powder under a pressure of 6 MPa to obtain a block green body;
[0048] Step 5: Place the block green body obtained in step 5 into a box furnace, heat it to 500° C. and keep it for 10 hours to debind, thereby obtaining a debinded green body;
[0049] Step 6: Place the debinding body obtained in step 5 into a box furnace, heat the box furnace to 1000°C at a rate of 5°C / min in an air atmosphere, then heat the debinding body to 1100°C-1140°C at a heating rate of 2°C / min and maintain for 10 hours, then cool it to 1000°C at a rate of 2°C / min, then cool it to 500°C at a rate of 5°C / min, turn off the program, and then naturally cool it to room temperature to obtain Z-type hexagonal ferrite sintered under air atmosphere conditions;
[0050] Step 7: Place the Z-type hexagonal ferrite obtained in step 6 into a tube furnace, introduce oxygen into the tube of the tube furnace at a flow rate of 200 mL / min to obtain an oxygen atmosphere, and at the same time, heat the tube furnace to 950°C at a rate of 5°C / min and keep it warm for 14 days, then cool it to 500°C at a rate of 5°C / min and turn off the program, and then naturally cool it to room temperature to obtain a Z-type hexagonal ferrite magnetoelectric coupling ceramic material Sr3Co 1.25 Cu 0.75 Fe 24 O 41 (as a comparative example).
[0051] Example 2: The chemical formula of the Z-type hexagonal ferrite magnetoelectric coupling ceramic material of this example is Ba 0.2 Sr 2.8 Co 1.25 Cu 0.75 Fe 24 O 41 The preparation method thereof is different from that of Example 1 in that step 1 and step 7 are replaced by the following operations:
[0052] The operation of step 1 is as follows: Press the Z-type hexagonal ferrite Ba 0.2 Sr 2.8 Co 1.25 Cu 0.75 Fe 24 O 41 0.5920 g of BaCO3, 6.2004 g of SrCO3, 1.5049 g of Co3O4, 0.9155 g of CuO and 28.7438 g of Fe2O3 were weighed in a stoichiometric ratio, and then put into a ball mill, and then 140 mL of 95% ethanol was added, the number of small balls in the ball mill was 30, and the ball mill was carried out at a speed of 400 r / min for 12 h; after the ball milling was completed, it was placed in an oven at a temperature of 90°C for 8 h to dry, and after drying, it was placed in a ball mill again, and ball milled at a speed of 500 r / min for 10 min to obtain a mixed powder;
[0053] The operation of step seven is as follows: the Z-type hexagonal ferrite sintered in the box furnace is placed in a tube furnace, oxygen is introduced into the furnace tube at a flow rate of 100 mL / min to obtain an oxygen atmosphere, and the tube furnace is heated to 950°C at a rate of 5°C / min and kept warm for 14 days, and then cooled to 500°C at a rate of 5°C / min to close the program, and then naturally cooled to room temperature to obtain the Z-type hexagonal ferrite magnetoelectric coupling ceramic material Ba 0.2 Sr 2.8 Co 1.25 Cu 0.75 Fe 24 O 41 .
[0054] The other steps and parameters of this embodiment are the same as those of Embodiment 1.
[0055] Example 3: The chemical formula of the Z-type hexagonal ferrite magnetoelectric coupling ceramic material of this example is Ba 0.6 Sr 2.4 Co 1.25 Cu 0.75 Fe 24 O 41 The preparation method thereof is different from that of Example 1 in that steps 1 and 7 are replaced by the following operations:
[0056] The operation of step 1 is as follows: Press the Z-type hexagonal ferrite Ba 0.6 Sr 2.4 Co 1.25 Cu 0.75 Fe 24 O 41 1.7760 g BaCO3, 5.3146 g SrCO3, 1.5049 g Co3O4, 0.9155 g CuO and 28.7438 g Fe2O3 were weighed in a stoichiometric ratio, and then put into a ball mill, and then 140 mL of 95% ethanol was added, the number of small balls in the ball mill was about 30, and the ball mill was milled at a speed of 400 r / min for 12 h; after the ball milling was completed, it was placed in an oven at a temperature of 90°C for 8 h for drying, and after drying, it was placed in a ball mill again, the number of small balls in the ball mill was about 30, and the ball mill was milled at a speed of 500 r / min for 10 min to obtain a mixed powder;
[0057] The operation of step seven is as follows: the Z-type hexagonal ferrite sintered in the box furnace is placed in a tube furnace, oxygen is introduced into the furnace tube at a flow rate of 100 mL / min to obtain an oxygen atmosphere, and the tube furnace is heated to 950°C at a rate of 5°C / min and kept warm for 14 days, and then cooled to 500°C at a rate of 5°C / min to close the program, and then naturally cooled to room temperature to obtain the Z-type hexagonal ferrite magnetoelectric coupling ceramic material Ba 0.6 Sr 2.4 Co 1.25 Cu 0.75 Fe 24 O 41 .
[0058] The other steps and parameters of this embodiment are the same as those of Embodiment 1.
[0059] Example 4: The chemical formula of the Z-type hexagonal ferrite magnetoelectric coupling ceramic material of this example is Ba 1.0 Sr 2.0 Co 1.25 Cu 0.75 Fe 24 O 41The preparation method thereof is different from that of Example 1 in that step 1 and step 7 are replaced by the following operations:
[0060] The operation of step 1 is as follows: Press the Z-type hexagonal ferrite Ba 1.0 Sr 2.0 Co 1.25 Cu 0.75 Fe 24 O 41 2.9600 g of BaCO3, 4.4289 g of SrCO3, 1.5049 g of Co3O4, 0.9155 g of CuO and 28.7438 g of Fe2O3 were weighed in a stoichiometric ratio, and then put into a ball mill, and then 140 mL of 95% ethanol was added, the number of small balls in the ball mill was about 30, and the ball mill was milled at a speed of 400 r / min for 12 h; after the ball milling was completed, it was placed in an oven at a temperature of 90°C for 8 h to dry, and after drying, it was placed in a ball mill again, the number of small balls in the ball mill was about 30, and the ball mill was milled at a speed of 500 r / min for 10 min to obtain a mixed powder;
[0061] The operation of step seven is as follows: the Z-type hexagonal ferrite sintered in the box furnace is placed in a tube furnace, oxygen is introduced into the furnace tube at an oxygen flow rate of about 100 mL / min to obtain an oxygen atmosphere, and the tube furnace is heated to 950°C at a rate of 5°C / min and kept warm for 14 days, and then cooled to 500°C at a rate of 5°C / min to close the program, and then naturally cooled to room temperature to obtain the Z-type hexagonal ferrite magnetoelectric coupling ceramic material Ba1Sr2Co 1.25 Cu 0.75 Fe 24 O 41 .
[0062] The other steps and parameters of this embodiment are the same as those of Embodiment 1.
[0063] Example 5: The chemical formula of the Z-type hexagonal ferrite magnetoelectric coupling ceramic material of this example is Ba 1.2 Sr 1.8 Co 1.25 Cu 0.75 Fe 24 O 41 The preparation method thereof is different from that of Example 1 in that step 1 and step 7 are replaced by the following operations:
[0064] The operation of step 1 is as follows: Press the Z-type hexagonal ferrite Ba 1.2 Sr 1.8 Co 1.25 Cu 0.75 Fe 24 O 413.5520 g BaCO3, 3.9859 g SrCO3, 1.5049 g Co3O4, 0.9155 g CuO and 28.7438 g Fe2O3 were weighed in a stoichiometric ratio, and then put into a ball mill, and then 140 mL of 95% ethanol was added, the number of small balls in the ball mill was about 30, and the ball mill was milled at a speed of 400 r / min for 12 h; after the ball milling was completed, it was placed in an oven at a temperature of 90°C for 8 h for drying, and after drying, it was placed in a ball mill again, the number of small balls in the ball mill was about 30, and the ball mill was milled at a speed of 500 r / min for 10 min to obtain a mixed powder;
[0065] The operation of step seven is as follows: the Z-type hexagonal ferrite sintered in the box furnace is placed in a tube furnace, oxygen is introduced into the furnace tube at a flow rate of 100 mL / min to obtain an oxygen atmosphere, and the tube furnace is heated to 950°C at a rate of 5°C / min and kept warm for 14 days, and then cooled to 500°C at a rate of 5°C / min to close the program, and then naturally cooled to room temperature to obtain the Z-type hexagonal ferrite magnetoelectric coupling ceramic material Ba 1.2 Sr 1.8 Co 1.25 Cu 0.75 Fe 24 O 41 .
[0066] The other steps and parameters of this embodiment are the same as those of Embodiment 1.
[0067] Example 6: The chemical formula of the Z-type hexagonal ferrite magnetoelectric coupling ceramic material of this example is Ba 1.4 Sr 1.6 Co 1.25 Cu 0.75 Fe 24 O 41 The preparation method thereof is different from that of Example 1 in that step 1 and step 7 are replaced by the following operations:
[0068] The operation of step 1 is as follows: Press the Z-type hexagonal ferrite Ba 1.4 Sr 1.6 Co 1.25 Cu 0.75 Fe 24 O 414.1440 g BaCO3, 3.5431 g SrCO3, 1.5049 g Co3O4, 0.9155 g CuO and 28.7438 g Fe2O3 were weighed in a stoichiometric ratio, and then put into a ball mill, and then 140 mL of 95% ethanol was added. The number of small balls in the ball mill was about 30, and the ball mill was milled at a speed of 400 r / min for 12 h; after the ball milling was completed, it was placed in an oven at a temperature of 90°C for 8 h and dried. After drying, it was placed in a ball mill again, and the number of small balls in the ball mill was about 30. It was ball milled at a speed of 500 r / min for 10 min to obtain a mixed powder;
[0069] The operation of step seven is as follows: the Z-type hexagonal ferrite sintered in the box furnace is placed in a tube furnace, oxygen is introduced into the furnace tube at a flow rate of 100 mL / min to obtain an oxygen atmosphere, and the tube furnace is heated to 950°C at a rate of 5°C / min and kept warm for 14 days, and then cooled to 500°C at a rate of 5°C / min to close the program, and then naturally cooled to room temperature to obtain Z-type hexagonal ferrite Ba annealed under oxygen atmosphere. 1.4 Sr 1.6 Co 1.25 Cu 0.75 Fe 24 O 41 .
[0070] The other steps and parameters of this embodiment are the same as those of Embodiment 1.
[0071] Embodiment 7: This embodiment is different from Embodiment 1 in that Step 1 and Step 7 are replaced by the following operations:
[0072] The operation of step 1 is as follows: Press the Z-type hexagonal ferrite Ba 1.5 Sr 1.5 Co 1.25 Cu 0.75 Fe 24 O 41 4.4400 g of BaCO3, 3.3217 g of SrCO3, 1.5049 g of Co3O4, 0.9155 g of CuO and 28.7438 g of Fe2O3 were weighed in a stoichiometric ratio, and then put into a ball mill, and then 140 mL of 95% ethanol was added, the number of small balls in the ball mill was about 30, and the ball mill was milled at a speed of 400 r / min for 12 h; after the ball milling was completed, it was placed in an oven at a temperature of 90°C for 8 h to dry, and after drying, it was placed in a ball mill again, the number of small balls in the ball mill was about 30, and the ball mill was milled at a speed of 500 r / min for 10 min to obtain a mixed powder;
[0073] The operation of step seven is as follows: the Z-type hexagonal ferrite sintered in the box furnace is placed in a tube furnace, oxygen is introduced into the furnace tube at a flow rate of 100 mL / min to obtain an oxygen atmosphere, and the tube furnace is heated to 950°C at a rate of 5°C / min and kept warm for 14 days, and then cooled to 500°C at a rate of 5°C / min to close the program, and then naturally cooled to room temperature to obtain the Z-type hexagonal ferrite magnetoelectric coupling ceramic material Ba 1.5 Sr 1.5 Co 1.25 Cu 0.75 Fe 24 O 41 .
[0074] The other steps and parameters of this embodiment are the same as those of Embodiment 1.
[0075] Embodiment 8: This embodiment is different from Embodiment 1 in that Step 1 and Step 7 are replaced by the following operations:
[0076] The operation of step 1 is as follows: Press the Z-type hexagonal ferrite Ba 1.6 Sr 1.4 Co 1.25 Cu 0.75 Fe 24 O 41 4.7360 g BaCO3, 3.1002 g SrCO3, 1.5049 g Co3O4, 0.9155 g CuO and 28.7438 g Fe2O3 were weighed in a stoichiometric ratio, and then put into a ball mill, and then 140 mL of 95% ethanol was added, the number of small balls in the ball mill was about 30, and the ball mill was milled at a speed of 400 r / min for 12 h; after the ball milling was completed, it was placed in an oven at a temperature of 90°C for 8 h for drying, and after drying, it was placed in a ball mill again, the number of small balls in the ball mill was about 30, and the ball mill was milled at a speed of 500 r / min for 10 min to obtain a mixed powder;
[0077] The operation of step seven is as follows: the Z-type hexagonal ferrite sintered in the box furnace is placed in a tube furnace, oxygen is introduced into the furnace tube at an oxygen flow rate of about 100 mL / min to obtain an oxygen atmosphere, and the tube furnace is heated to 950°C at a rate of 5°C / min and kept warm for 14 days, and then cooled to 500°C at a rate of 5°C / min to close the program, and then naturally cooled to room temperature to obtain the Z-type hexagonal ferrite magnetoelectric coupling ceramic material Ba. 1.6 Sr 1.4 Co 1.25 Cu 0.75 Fe 24 O 41 .
[0078] The other steps and parameters of this embodiment are the same as those of Embodiment 1.
[0079] Embodiment 9: This embodiment is different from Embodiment 1 in that Step 1 and Step 7 are replaced by the following operations:
[0080] The operation of step 1 is as follows: Press the Z-type hexagonal ferrite Ba 1.8 Sr 1.2 Co 1.25 Cu 0.75 Fe 24 O 41 5.3280 g of BaCO3, 2.6573 g of SrCO3, 1.5049 g of Co3O4, 0.9155 g of CuO and 28.7438 g of Fe2O3 were weighed in a stoichiometric ratio, and then put into a ball mill, and then 140 mL of ethanol with a mass percentage concentration of 95% was added, the number of small balls in the ball mill was about 30, and the ball mill was milled at a speed of 400 r / min for 12 h; after the ball milling was completed, it was placed in an oven at a temperature of 90°C for 8 h for drying, and after drying, it was placed in a ball mill again, the number of small balls in the ball mill was about 30, and the ball mill was milled at a speed of 500 r / min for 10 min to obtain a mixed powder;
[0081] The operation of step seven is as follows: the Z-type hexagonal ferrite sintered in the box furnace is placed in a tube furnace, oxygen is introduced into the furnace tube at a flow rate of 100 mL / min to obtain an oxygen atmosphere, and the tube furnace is heated to 950°C at a rate of 5°C / min and kept warm for 14 days, and then cooled to 500°C at a rate of 5°C / min to close the program, and then naturally cooled to room temperature to obtain the Z-type hexagonal ferrite magnetoelectric coupling ceramic material Ba 1.8 Sr 1.2 Co 1.25 Cu 0.75 Fe 24 O 41 .
[0082] The other steps and parameters of this embodiment are the same as those of Embodiment 1.
[0083] Embodiment 10: This embodiment differs from Embodiment 1 in that Step 1 and Step 7 are replaced by the following operations:
[0084] The operation of step 1 is as follows: Press the Z-type hexagonal ferrite Ba 2.2 Sr 0.8 Co 1.5 Cu 0.5 Fe 24 O 416.5121 g of BaCO3, 1.7715 g of SrCO3, 1.5049 g of Co3O4, 0.9155 g of CuO and 28.7438 g of Fe2O3 were weighed in a stoichiometric ratio, and then put into a ball mill, and then 140 mL of 95% ethanol was added, the number of small balls in the ball mill was about 30, and the ball mill was milled at a speed of 400 r / min for 12 h; after the ball milling was completed, it was placed in an oven at a temperature of 90°C for 8 h for drying, and after drying, it was placed in a ball mill again, the number of small balls in the ball mill was about 30, and the ball mill was milled at a speed of 500 r / min for 10 min to obtain a mixed powder;
[0085] The operation of step seven is as follows: the Z-type hexagonal ferrite sintered in the box furnace is placed in a tube furnace, oxygen is introduced into the furnace tube at a flow rate of 100 mL / min to obtain an oxygen atmosphere, and the tube furnace is heated to 950°C at a rate of 5°C / min and kept warm for 14 days, and then cooled to 500°C at a rate of 5°C / min to close the program, and then naturally cooled to room temperature to obtain the Z-type hexagonal ferrite magnetoelectric coupling ceramic material Ba 2.2 Sr 0.8 Co 1.25 Cu 0.75 Fe 24 O 41 .
[0086] The other steps and parameters of this embodiment are the same as those of Embodiment 1.
[0087] Embodiment 11: This embodiment differs from Embodiment 1 in that Step 1 and Step 7 are replaced by the following operations:
[0088] The operation of step 1 is as follows: Press the Z-type hexagonal ferrite Ba 2.6 Sr 0.4 Co 1.25 Cu 0.75 Fe 24 O 41 7.6961 g BaCO3, 0.8857 g SrCO3, 1.5049 g Co3O4, 0.9155 g CuO and 28.7438 g Fe2O3 were weighed in a stoichiometric ratio and put into a ball mill. Then, 140 mL of 95% ethanol was added. The number of small balls in the ball mill was about 30. The mixture was ball milled at a speed of 400 r / min for 12 h. After the ball milling was completed, the mixture was placed in an oven at a temperature of 90°C for 8 h for drying. After drying, the mixture was placed in a ball mill again. The number of small balls in the ball mill was about 30. The mixture was ball milled at a speed of 500 r / min for 10 min to obtain a mixed powder.
[0089] The operation of step seven is as follows: the Z-type hexagonal ferrite sintered in the box furnace is placed in a tube furnace, oxygen is introduced into the furnace tube at a flow rate of 100 mL / min to obtain an oxygen atmosphere, and the tube furnace is heated to 950°C at a rate of 5°C / min and kept warm for 14 days, and then cooled to 500°C at a rate of 5°C / min to close the program, and then naturally cooled to room temperature to obtain the Z-type hexagonal ferrite magnetoelectric coupling ceramic material Ba 2.6 Sr 0.4 Co 1.25 Cu 0.75 Fe 24 O 41 .
[0090] The other steps and parameters of this embodiment are the same as those of Embodiment 1.
[0091] Embodiment 12: This embodiment differs from Embodiment 1 in that Step 1 and Step 7 are replaced by the following operations:
[0092] The operation of step 1 is as follows: Press the Z-type hexagonal ferrite Ba3Co 1.25 Cu 0.75 Fe 24 O 41 8.8801 g BaCO3, 0 g SrCO3, 1.5049 g Co3O4, 0.9155 g CuO, and 28.7438 g Fe2O3 were weighed in a stoichiometric ratio, and put into a ball mill, and then 140 mL of 95% ethanol was added, and the number of small balls in the ball mill was about 30. The ball mill was milled at a speed of 400 r / min for 12 h; after the ball milling was completed, it was placed in an oven at a temperature of 90°C for 8 h for drying, and after drying, it was placed in a ball mill again, and the number of small balls in the ball mill was about 30. The ball mill was milled at a speed of 500 r / min for 10 min to obtain a mixed powder;
[0093] The operation of step seven is as follows: the Z-type hexagonal ferrite sintered in the box furnace is placed in a tube furnace, oxygen is introduced into the furnace tube at a flow rate of 100 mL / min to obtain an oxygen atmosphere, and the tube furnace is heated to 950°C at a rate of 5°C / min and kept warm for 14 days, and then cooled to 500°C at a rate of 5°C / min to close the program, and then naturally cooled to room temperature to obtain the Z-type hexagonal ferrite magnetoelectric coupling ceramic material Ba3Co 1.25 Cu 0.75 Fe 24 O 41 .
[0094] The other steps and parameters of this embodiment are the same as those of Embodiment 1.
[0095] The Z-type hexagonal ferrites prepared in Examples 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, and 12 were tested by scanning electron microscopy. 1.25 Cu 0.75 Fe 24 O 41, Ba 0.2 Sr 2.8 Co 1.25 Cu 0.75 Fe 24 O 41, Ba 0.6 Sr 2.4 Co 1.25 Cu 0.75 Fe 24 O 41, Ba 1.0 Sr 2.0 Co 1.25 Cu 0.75 Fe 24 O 41, Ba 1.2 Sr 1.8 Co 1.25 Cu 0.75 Fe 24 O 41, Ba 1.4 Sr 1.6 Co 1.25 Cu 0.75 Fe 24 O 41, Ba 1.5 Sr 1.5 Co 1.25 Cu 0.75 Fe 24 O 41, Ba 1.6 Sr 1.4 Co 1.25 Cu 0.75 Fe 24 O 41, Ba 1.8 Sr 1.2 Co 1.25 Cu 0.75 Fe 24 O 41, Ba 2.2 Sr 0.8 Co 1.25 Cu 0.75 Fe 24 O 41, Ba 2.6 Sr 0.4 Co 1.25 Cu 0.75 Fe 24 O41, Ba3Co 1.25 Cu 0.75 Fe 24 O 41 The scanning electron microscope pictures are as follows Figure 1 shown.
[0096] from Figure 1 It can be seen that the test sample exhibits a hexagonal flake structure, which is consistent with the typical characteristics of Z-type hexagonal ferrite.
[0097] XRD analysis was performed on the Z-type hexagonal ferrite prepared in Examples 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, and 12, and the obtained XRD spectra were as follows: Figure 2 As shown, from Figure 2 It can be seen that Sr3Co 1.25 Cu 0.75 Fe 24 O 41, Ba 0.2 Sr 2.8 Co 1.25 Cu 0.75 Fe 24 O 41, Ba 0.6 Sr 2.4 Co 1.25 Cu 0.75 Fe 24 O 41, Ba 1.0 Sr 2.0 Co 1.25 Cu 0.75 Fe 24 O 41, Ba 1.2 Sr 1.8 Co 1.25 Cu 0.75 Fe 24 O 41, Ba 1.4 Sr 1.6 Co 1.25 Cu 0.75 Fe 24 O 41, Ba 1.5 Sr 1.5 Co 1.25 Cu 0.75 Fe 24 O 41, Ba 1.6 Sr 1.4 Co 1.25 Cu 0.75 Fe 24 O 41, Ba 1.8 Sr1.2 Co 1.25 Cu 0.75 Fe 24 O 41, Ba 2.2 Sr 0.8 Co 1.25 Cu 0.75 Fe 24 O 41, Ba 2.6 Sr 0.4 Co 1.25 Cu 0.75 Fe 24 O 41, Ba3Co 1.25 Cu 0.75 Fe 24 O 41 All exhibit the characteristic Z-type hexagonal ferrite spatial configuration.
[0098] For Examples 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12Sr3Co 1.25 Cu 0.75 Fe 24 O 41, Ba 0.2 Sr 2.8 Co 1.25 Cu 0.75 Fe 24 O 41, Ba 0.6 Sr 2.4 Co 1.25 Cu 0.75 Fe 24 O 41, Ba 1.0 Sr 2.0 Co 1.25 Cu 0.75 Fe 24 O 41, Ba 1.2 Sr 1.8 Co 1.25 Cu 0.75 Fe 24 O 41, Ba 1.4 Sr 1.6 Co 1.25 Cu 0.75 Fe 24 O 41, Ba 1.5 Sr 1.5 Co 1.25 Cu 0.75 Fe 24 O 41, Ba 1.6 Sr1.4 Co 1.25 Cu 0.75 Fe 24 O 41, Ba 1.8 Sr 1.2 Co 1.25 Cu 0.75 Fe 24 O 41, Ba 2.2 Sr 0.8 Co 1.25 Cu 0.75 Fe 24 O 41, Ba 2.6 Sr 0.4 Co 1.25 Cu 0.75 Fe 24 O 41, Ba3Co 1.25 Cu 0.75 Fe 24 O 41 The magnetic field-induced magnetoelectric current under positive and negative polarization electric fields is as follows: Figure 3-14 shown.
[0099] from Figure 3 , Fig.12 , Fig.13 and Fig.14 It can be seen that the magnetoelectric coupling coefficients of Example 1, Example 10, Example 11 and Example 12 are all 0 under the forward polarization electric field or the reverse polarization electric field, indicating that Example 1 (Sr3Co 1.25 Cu 0.75 Fe 24 O 41 ), Example 10 (Ba 2.2 Sr 0.8 Co 1.25 Cu 0.75 Fe 24 O 41 ), Example 11 (Ba 2.6 Sr 0.4 Co 1.25 Cu 0.75 Fe 24 O 41 ), Example 12 (Ba3Co 1.25 Cu 0.75 Fe 24 O 41 )Z-type hexagonal ferrite does not exhibit magneto-electric coupling performance, either at low temperatures or at room temperature and above.
[0100] from Figure 4It can be seen that Example 2 (Ba 0.2 Sr 2.8 Co 1.25 Cu 0.75 Fe 24 O 41 )It exhibits magnetoelectric coupling performance both at low temperatures and at room temperature and above.
[0101] Under the positive polarization electric field, in the process of sweeping the field from 2kOe to 0 and then to -2kOe, Example 2 (Ba 0.2 Sr 2.8 Co 1.25 Cu 0.75 Fe 24 O 41 ) The dynamic magnetoelectric coupling coefficient of the sample presents a symmetrical shape about the origin (0, 0); Similarly, in the process of the scanning field changing from -2kOe to 0 and then to 2kOe, Example 2 (Ba 0.2 Sr 2.8 Co 1.25 Cu 0.75 Fe 24 O 41 The dynamic magnetoelectric coupling coefficient of the sample ) also presents a symmetrical shape about the origin (0, 0); the difference is that when the scanning direction changes, Example 2 (Ba 0.2 Sr 2.8 Co 1.25 Cu 0.75 Fe 24 O 41 ) The direction of the magnetoelectric coupling coefficient of the sample is changed, so by changing the direction of the scanning field, the embodiment 2 (Ba 0.2 Sr 2.8 Co 1.25 Cu 0.75 Fe 24 O 41 ) Regulation of the direction of the sample's magnetoelectric coupling coefficient.
[0102] Under the reverse polarization electric field condition, in the process of sweeping the field from 2kOe to 0 and then to -2kOe, Example 2 (Ba 0.2 Sr 2.8 Co 1.25 Cu 0.75 Fe 24 O 41 ) The dynamic magnetoelectric coupling coefficient of the sample presents a symmetrical shape about the origin (0, 0); Similarly, in the process of changing the scanning field from -2kOe to 0 and then to 2kOe, Example 2 (Ba 0.2 Sr 2.8 Co 1.25 Cu 0.75Fe 24 O 41 The dynamic magnetoelectric coupling coefficient of the sample ) also presents a symmetrical shape about the origin (0, 0); the difference is that when the scanning direction changes, Example 2 (Ba 0.2 Sr 2.8 Co 1.25 Cu 0.75 Fe 24 O 41 ) The direction of the magnetoelectric coupling coefficient of the sample is changed, so under the condition of reverse polarization electric field, the embodiment 2 (Ba 0.2 Sr 2.8 Co 1.25 Cu 0.75 Fe 24 O 41 ) Regulation of the magnetoelectric coupling coefficient of the sample.
[0103] In summary, in the forward polarization electric field and the reverse polarization electric field, Example 2 (Ba 0.2 Sr 2.8 Co 1.25 Cu 0.75 Fe 24 O 41 ) The magnetoelectric coupling coefficient of the sample changes with the scanning field. It can be found that under the same scanning field conditions, under different polarization electric field conditions, Example 2 (Ba 0.2 Sr 2.8 Co 1.25 Cu 0.75 Fe 24 O 41 ) The direction of the magnetoelectric coupling coefficient of the sample is opposite. 0.2 Sr 2.8 Co 1.25 Cu 0.75 Fe 24 O 41 ) The magnetoelectric coupling tolerance temperature of the sample can be seen in Example 2 (Ba 0.2 Sr 2.8 Co 1.25 Cu 0.75 Fe 24 O 41 ) has a magnetoelectric coupling tolerance temperature of 320K, which is a breakthrough in the magnetoelectric coupling performance under room temperature conditions. 0.2 Sr 2.8 Co 1.25 Cu 0.75 Fe 24 O 41 )The dynamic magnetoelectric coupling coefficient of the sample under low temperature conditions reaches up to 0.12mV / cm Oe.
[0104] Therefore, Example 2 (Ba 0.2 Sr 2.8 Co 1.25 Cu 0.75 Fe 24 O 41 The magnetoelectric coupling coefficient of the sample can be controlled by the direction of the external scanning field and the direction of the prepolarization electric field. It has potential application advantages in the field of non-volatile storage based on magnetoelectric coupling devices.
[0105] from Figure 5 It can be seen that Example 3 (Ba 0.6 Sr 2.4 Co 1.25 Cu 0.75 Fe 24 O 41 )It exhibits magnetoelectric coupling performance both at low temperatures and at room temperature and above.
[0106] Under the positive polarization electric field, in the process of sweeping the field from 2kOe to 0 and then to -2kOe, Example 3 (Ba 0.6 Sr 2.4 Co 1.25 Cu 0.75 Fe 24 O 41 ) The dynamic magnetoelectric coupling coefficient of the sample presents a symmetrical shape about the origin (0, 0); Similarly, in the process of changing the scanning field from -2kOe to 0 and then to 2kOe, Example 3 (Ba 0.6 Sr 2.4 Co 1.25 Cu 0.75 Fe 24 O 41 The dynamic magnetoelectric coupling coefficient of the sample ) also presents a symmetrical shape about the origin (0, 0); the difference is that when the scanning direction changes, Example 3 (Ba 0.6 Sr 2.4 Co 1.25 Cu 0.75 Fe 24 O 41 ) The direction of the magnetoelectric coupling coefficient of the sample changes, so by changing the direction of the scanning field, the embodiment 3 (Ba 0.6 Sr 2.4 Co 1.25 Cu 0.75 Fe 24 O 41 ) Regulation of the direction of the sample's magnetoelectric coupling coefficient.
[0107] Under the reverse polarization electric field condition, in the process of sweeping the field from 2kOe to 0 and then to -2kOe, Example 3 (Ba0.6 Sr 2.4 Co 1.25 Cu 0.75 Fe 24 O 41 ) The dynamic magnetoelectric coupling coefficient of the sample presents a symmetrical shape about the origin (0, 0); Similarly, in the process of changing the scanning field from -2kOe to 0 and then to 2kOe, Example 3 (Ba 0.6 Sr 2.4 Co 1.25 Cu 0.75 Fe 24 O 41 The dynamic magnetoelectric coupling coefficient of the sample ) also presents a symmetrical shape about the origin (0, 0); the difference is that when the scanning direction changes, Example 3 (Ba 0.6 Sr 2.4 Co 1.25 Cu 0.75 Fe 24 O 41 ) The direction of the magnetoelectric coupling coefficient of the sample is changed, so under the condition of reverse polarization electric field, the embodiment 3 (Ba 0.6 Sr 2.4 Co 1.25 Cu 0.75 Fe 24 O 41 ) Regulation of the magnetoelectric coupling coefficient of the sample.
[0108] In summary, in the forward polarization electric field and the reverse polarization electric field, Example 3 (Ba 0.6 Sr 2.4 Co 1.25 Cu 0.75 Fe 24 O 41 ) The magnetoelectric coupling coefficient of the sample changes with the scanning field. It can be found that under the same scanning field conditions, under different polarization electric field conditions, Example 3 (Ba 0.6 Sr 2.4 Co 1.25 Cu 0.75 Fe 24 O 41 )The directions of the magnetoelectric coupling coefficients of the samples are opposite.
[0109] Therefore, Example 3 (Ba 0.6 Sr 2.4 Co 1.25 Cu 0.75 Fe 24 O 41) The magnetoelectric coupling coefficient of the sample can be controlled by the direction of the external scanning field and the direction of the prepolarization electric field. It has potential application advantages in the field of non-volatile storage based on magnetoelectric coupling. 0.6 Sr 2.4 Co 1.25 Cu 0.75 Fe 24 O 41 ) The magnetoelectric coupling tolerance temperature of the sample can be seen that Example 3 (Ba 0.6 Sr 2.4 Co 1.25 Cu 0.75 Fe 24 O 41 ) has a magnetoelectric coupling tolerance temperature of 350K, which is a breakthrough in the magnetoelectric coupling performance under room temperature conditions. 0.6 Sr 2.4 Co 1.25 Cu 0.75 Fe 24 O 41 The dynamic magnetoelectric coupling coefficient of the sample under low temperature conditions reaches up to 4.11mV / cm Oe.
[0110] from Figure 6 It can be seen that Example 4 (Ba 1.0 Sr 2.0 Co 1.25 Cu 0.75 Fe 24 O 41 )It exhibits magnetoelectric coupling performance both at low temperatures and at room temperature and above.
[0111] Under the positive polarization electric field, in the process of sweeping the field from 2kOe to 0 and then to -2kOe, Example 4 (Ba 1.0 Sr 2.0 Co 1.25 Cu 0.75 Fe 24 O 41 ) The dynamic magnetoelectric coupling coefficient of the sample presents a shape symmetrical about the origin (0, 0); Similarly, in the process of changing the scanning field from -2kOe to 0 and then to 2kOe, Example 4 (Ba 1.0 Sr 2.0 Co 1.25 Cu 0.75 Fe 24 O 41 The dynamic magnetoelectric coupling coefficient of the sample ) also presents a symmetrical shape about the origin (0, 0); the difference is that when the scanning direction changes, Example 4 (Ba 1.0 Sr 2.0 Co1.25 Cu 0.75 Fe 24 O 41 ) The direction of the magnetoelectric coupling coefficient of the sample changes, so by changing the direction of the scanning field, the embodiment 4 (Ba 1.0 Sr 2.0 Co 1.25 Cu 0.75 Fe 24 O 41 ) Regulation of the direction of the sample's magnetoelectric coupling coefficient.
[0112] Under the reverse polarization electric field condition, in the process of sweeping the field from 2kOe to 0 and then to -2kOe, Example 4 (Ba 1.0 Sr 2.0 Co 1.25 Cu 0.75 Fe 24 O 41 ) The dynamic magnetoelectric coupling coefficient of the sample presents a symmetrical shape about the origin (0, 0); Similarly, in the process of changing the scanning field from -2kOe to 0 and then to 2kOe, Example 4 (Ba 1.0 Sr 2.0 Co 1.25 Cu 0.75 Fe 24 O 41 The dynamic magnetoelectric coupling coefficient of the sample ) also presents a symmetrical shape about the origin (0, 0); the difference is that when the scanning direction changes, Example 4 (Ba 1.0 Sr 2.0 Co 1.25 Cu 0.75 Fe 24 O 41 ) The direction of the magnetoelectric coupling coefficient of the sample is changed, so under the condition of reverse polarization electric field, the embodiment 4 (Ba 1.0 Sr 2.0 Co 1.25 Cu 0.75 Fe 24 O 41 ) Regulation of the magnetoelectric coupling coefficient of the sample.
[0113] In summary, the change of the magnetoelectric coupling coefficient of the sample under the forward polarization electric field and the reverse polarization electric field with the scanning field can be found that under the same scanning field conditions, Example 4 (Ba 1.0 Sr 2.0 Co 1.25 Cu 0.75 Fe 24 O 41 )The directions of the magnetoelectric coupling coefficients of the samples are opposite.
[0114] Therefore, Example 4 (Ba 1.0 Sr 2.0 Co 1.25 Cu 0.75 Fe 24 O 41 ) The magnetoelectric coupling coefficient of the sample can be controlled by the direction of the external scanning field and the direction of the prepolarization electric field. It has potential application advantages in the field of non-volatile storage based on magnetoelectric coupling. 1.0 Sr 2.0 Co 1.25 Cu 0.75 Fe 24 O 41 ) The magnetoelectric coupling tolerance temperature of the sample can be seen that Example 4 (Ba 1.0 Sr 2.0 Co 1.25 Cu 0.75 Fe 24 O 41 ) has a magnetoelectric coupling tolerance temperature of 330K, which is a breakthrough in the magnetoelectric coupling performance under room temperature conditions. 1.0 Sr 2.0 Co 1.25 Cu 0.75 Fe 24 O 41 The dynamic magnetoelectric coupling coefficient of the sample under low temperature conditions reaches up to 4.84mV / cm Oe.
[0115] from Figure 7 It can be seen that Example 5 (Ba 1.2 Sr 1.8 Co 1.25 Cu 0.75 Fe 24 O 41 )It exhibits magnetoelectric coupling performance both at low temperatures and at room temperature and above.
[0116] Under the positive polarization electric field, in the process of sweeping the field from 2kOe to 0 and then to -2kOe, Example 5 (Ba 1.2 Sr 1.8 Co 1.25 Cu 0.75 Fe 24 O 41 ) The dynamic magnetoelectric coupling coefficient of the sample presents a shape symmetrical about the origin (0, 0); Similarly, in the process of changing the scanning field from -2kOe to 0 and then to 2kOe, Example 5 (Ba 1.2 Sr 1.8 Co 1.25 Cu 0.75Fe 24 O 41 The dynamic magnetoelectric coupling coefficient of the sample ) also presents a symmetrical shape about the origin (0, 0); the difference is that when the scanning direction changes, Example 5 (Ba 1.2 Sr 1.8 Co 1.25 Cu 0.75 Fe 24 O 41 ) The direction of the magnetoelectric coupling coefficient of the sample changes, so by changing the direction of the scanning field, the embodiment 5 (Ba 1.2 Sr 1.8 Co 1.25 Cu 0.75 Fe 24 O 41 ) Regulation of the direction of the sample's magnetoelectric coupling coefficient.
[0117] Under the reverse polarization electric field condition, in the process of sweeping the field from 2kOe to 0 and then to -2kOe, Example 5 (Ba 1.2 Sr 1.8 Co 1.25 Cu 0.75 Fe 24 O 41 ) The dynamic magnetoelectric coupling coefficient of the sample presents a symmetrical shape about the origin (0, 0); Similarly, in the process of changing the scanning field from -2kOe to 0 and then to 2kOe, Example 5 (Ba 1.2 Sr 1.8 Co 1.25 Cu 0.75 Fe 24 O 41 The dynamic magnetoelectric coupling coefficient of the sample ) also presents a symmetrical shape about the origin (0, 0); the difference is that when the scanning direction changes, Example 5 (Ba 1.2 Sr 1.8 Co 1.25 Cu 0.75 Fe 24 O 41 ) The direction of the magnetoelectric coupling coefficient of the sample is changed, so under the condition of reverse polarization electric field, the direction of the field scanning can be changed to achieve the embodiment 5 (Ba 1.2 Sr 1.8 Co 1.25 Cu 0.75 Fe 24 O 41 ) Regulation of the magnetoelectric coupling coefficient of the sample.
[0118] In summary, in the forward polarization electric field and the reverse polarization electric field, Example 5 (Ba 1.2 Sr 1.8 Co1.25 Cu 0.75 Fe 24 O 41 ) The magnetoelectric coupling coefficient of the sample changes with the scanning field. It can be found that under the same scanning field conditions, under different polarization electric field conditions, Example 5 (Ba 1.2 Sr 1.8 Co 1.25 Cu 0.75 Fe 24 O 41 )The directions of the magnetoelectric coupling coefficients of the samples are opposite.
[0119] Therefore, Example 5 (Ba 1.2 Sr 1.8 Co 1.25 Cu 0.75 Fe 24 O 41 ) The magnetoelectric coupling coefficient of the sample can be regulated by the direction of the external scanning field and the direction of the prepolarization electric field. It has potential application advantages in the field of non-volatile storage based on magnetoelectric coupling. 1.2 Sr 1.8 Co 1.25 Cu 0.75 Fe 24 O 41 ) The magnetoelectric coupling tolerance temperature of the sample can be seen that Example 5 (Ba 1.2 Sr 1.8 Co 1.25 Cu 0.75 Fe 24 O 41 )'s magnetoelectric coupling tolerance temperature reaches 330K, breaking through the magnetoelectric coupling performance under room temperature. Example 5 (Ba 1.2 Sr 1.8 Co 1.25 Cu 0.75 Fe 24 O 41 The dynamic magnetoelectric coupling coefficient of the sample under low temperature conditions reaches up to 5.07mV / cm Oe.
[0120] from Figure 8 It can be seen that Example 6 (Ba 1.4 Sr 1.6 Co 1.25 Cu 0.75 Fe 24 O 41 )It exhibits magnetoelectric coupling performance both at low temperatures and at room temperature and above.
[0121] Under the positive polarization electric field, in the process of sweeping the field from 2kOe to 0 and then to -2kOe, Example 6 (Ba1.4 Sr 1.6 Co 1.25 Cu 0.75 Fe 24 O 41 ) The dynamic magnetoelectric coupling coefficient of the sample presents a symmetrical shape about the origin (0, 0); Similarly, in the process of changing the scanning field from -2kOe to 0 and then to 2kOe, Example 6 (Ba 1.4 Sr 1.6 Co 1.25 Cu 0.75 Fe 24 O 41 The dynamic magnetoelectric coupling coefficient of the sample ) also presents a symmetrical shape about the origin (0, 0); the difference is that when the scanning direction changes, Example 6 (Ba 1.4 Sr 1.6 Co 1.25 Cu 0.75 Fe 24 O 41 ) The direction of the magnetoelectric coupling coefficient of the sample is changed, so by changing the direction of the scanning field, the embodiment 6 (Ba 1.4 Sr 1.6 Co 1.25 Cu 0.75 Fe 24 O 41 ) Regulation of the direction of the sample's magnetoelectric coupling coefficient.
[0122] Under the reverse polarization electric field condition, in the process of sweeping the field from 2kOe to 0 and then to -2kOe, Example 6 (Ba 1.4 Sr 1.6 Co 1.25 Cu 0.75 Fe 24 O 41 ) The dynamic magnetoelectric coupling coefficient of the sample presents a symmetrical shape about the origin (0, 0); Similarly, in the process of changing the scanning field from -2kOe to 0 and then to 2kOe, Example 6 (Ba 1.4 Sr 1.6 Co 1.25 Cu 0.75 Fe 24 O 41 The dynamic magnetoelectric coupling coefficient of the sample ) also presents a symmetrical shape about the origin (0, 0); the difference is that when the scanning direction changes, Example 6 (Ba 1.4 Sr 1.6 Co 1.25 Cu 0.75 Fe 24 O 41) The direction of the magnetoelectric coupling coefficient of the sample is changed, so under the condition of reverse polarization electric field, the embodiment 6 (Ba 1.4 Sr 1.6 Co 1.25 Cu 0.75 Fe 24 O 41 ) Regulation of the magnetoelectric coupling coefficient of the sample.
[0123] In summary, Example 6 (Ba 1.4 Sr 1.6 Co 1.25 Cu 0.75 Fe 24 O 41 ) The magnetoelectric coupling coefficient of the sample changes with the scanning field. It can be found that under the same scanning field conditions, under different polarization electric field conditions, Example 6 (Ba 1.4 Sr 1.6 Co 1.25 Cu 0.75 Fe 24 O 41 )The directions of the magnetoelectric coupling coefficients of the samples are opposite.
[0124] Therefore, Example 6 (Ba 1.4 Sr 1.6 Co 1.25 Cu 0.75 Fe 24 O 41 ) The magnetoelectric coupling coefficient of the sample can be controlled by the direction of the external scanning field and the direction of the prepolarization electric field. It has potential application advantages in the field of non-volatile storage based on magnetoelectric coupling. 1.4 Sr 1.6 Co 1.25 Cu 0.75 Fe 24 O 41 ) The magnetoelectric coupling tolerance temperature of the sample can be seen that Example 6 (Ba 1.4 Sr 1.6 Co 1.25 Cu 0.75 Fe 24 O 41 )'s magnetoelectric coupling tolerance temperature fails to exceed room temperature, and does not have the magnetoelectric coupling performance under room temperature conditions. 1.4 Sr 1.6 Co 1.25 Cu 0.75 Fe 24 O 41 The dynamic magnetoelectric coupling coefficient of the sample under low temperature conditions reaches up to 5.29mV / cm Oe.
[0125] from Fig. 9 It can be seen that Example 7 (Ba 1.5 Sr 1.5 Co 1.25 Cu 0.75 Fe 24 O 41 )It exhibits magnetoelectric coupling performance both at low temperatures and at room temperature and above.
[0126] Under the positive polarization electric field, in the process of sweeping the field from 2kOe to 0 and then to -2kOe, Example 7 (Ba 1.5 Sr 1.5 Co 1.25 Cu 0.75 Fe 24 O 41 ) The dynamic magnetoelectric coupling coefficient of the sample presents a symmetrical shape about the origin (0, 0); Similarly, in the process of changing the scanning field from -2kOe to 0 and then to 2kOe, Example 7 (Ba 1.5 Sr 1.5 Co 1.25 Cu 0.75 Fe 24 O 41 ) samples also present a symmetrical shape about the origin (0, 0); the difference is that when the scanning direction changes, Example 7 (Ba 1.5 Sr 1.5 Co 1.25 Cu 0.75 Fe 24 O 41 ) The direction of the magnetoelectric coupling coefficient of the sample is changed, so by changing the direction of the scanning field, the embodiment 7 (Ba 1.5 Sr 1.5 Co 1.25 Cu 0.75 Fe 24 O 41 ) Regulation of the direction of the sample's magnetoelectric coupling coefficient.
[0127] Under the reverse polarization electric field condition, in the process of sweeping the field from 2kOe to 0 and then to -2kOe, Example 7 (Ba 1.5 Sr 1.5 Co 1.25 Cu 0.75 Fe 24 O 41 ) The dynamic magnetoelectric coupling coefficient of the sample presents a symmetrical shape about the origin (0, 0); Similarly, in the process of changing the scanning field from -2kOe to 0 and then to 2kOe, Example 7 (Ba 1.5 Sr1.5 Co 1.25 Cu 0.75 Fe 24 O 41 ) samples also present a symmetrical shape about the origin (0, 0); the difference is that when the scanning direction changes, Example 7 (Ba 1.5 Sr 1.5 Co 1.25 Cu 0.75 Fe 24 O 41 ) The direction of the magnetoelectric coupling coefficient of the sample is changed, so under the condition of reverse polarization electric field, the embodiment 7 (Ba 1.5 Sr 1.5 Co 1.25 Cu 0.75 Fe 24 O 41 ) Regulation of the magnetoelectric coupling coefficient of the sample.
[0128] In summary, Example 7 (Ba 1.5 Sr 1.5 Co 1.25 Cu 0.75 Fe 24 O 41 ) The magnetoelectric coupling coefficient changes with the scanning field. It can be found that under the same scanning field conditions, under different polarization electric field conditions, Example 7 (Ba 1.5 Sr 1.5 Co 1.25 Cu 0.75 Fe 24 O 41 )The directions of the magnetoelectric coupling coefficients of the samples are opposite.
[0129] Therefore, Example 7 (Ba 1.5 Sr 1.5 Co 1.25 Cu 0.75 Fe 24 O 41 ) The magnetoelectric coupling coefficient of the sample can be controlled by the direction of the external scanning field and the direction of the prepolarization electric field. It has potential application advantages in the field of non-volatile storage based on magnetoelectric coupling. 1.5 Sr 1.5 Co 1.25 Cu 0.75 Fe 24 O 41 ) The magnetoelectric coupling tolerance temperature of the sample can be seen that Example 7 (Ba 1.5 Sr 1.5 Co 1.25 Cu0.75 Fe 24 O 41 )'s magnetoelectric coupling tolerance temperature fails to exceed room temperature, and does not have the magnetoelectric coupling performance under room temperature conditions. 1.5 Sr 1.5 Co 1.25 Cu 0.75 Fe 24 O 41 The dynamic magnetoelectric coupling coefficient of the sample under low temperature conditions reaches up to 9.13mV / cm Oe.
[0130] from Fig.10 It can be seen that Example 8 (Ba 1.6 Sr 1.4 Co 1.25 Cu 0.75 Fe 24 O 41 )It exhibits magnetoelectric coupling performance both at low temperatures and at room temperature and above.
[0131] Under the positive polarization electric field, in the process of sweeping the field from 2kOe to 0 and then to -2kOe, Example 8 (Ba 1.6 Sr 1.4 Co 1.25 Cu 0.75 Fe 24 O 41 ) The dynamic magnetoelectric coupling coefficient of the sample presents a symmetrical shape about the origin (0, 0); Similarly, in the process of changing the scanning field from -2kOe to 0 and then to 2kOe, Example 8 (Ba 1.6 Sr 1.4 Co 1.25 Cu 0.75 Fe 24 O 41 The dynamic magnetoelectric coupling coefficient of the sample ) also presents a symmetrical shape about the origin (0, 0); the difference is that when the scanning direction changes, Example 8 (Ba 1.6 Sr 1.4 Co 1.25 Cu 0.75 Fe 24 O 41 ) The direction of the magnetoelectric coupling coefficient of the sample changes, so by changing the direction of the scanning field, the embodiment 8 (Ba 1.6 Sr 1.4 Co 1.25 Cu 0.75 Fe 24 O 41 ) Regulation of the direction of the sample's magnetoelectric coupling coefficient.
[0132] Under the reverse polarization electric field condition, in the process of sweeping the field from 2kOe to 0 and then to -2kOe, Example 8 (Ba 1.6 Sr 1.4 Co 1.25 Cu 0.75 Fe 24 O 41 ) The dynamic magnetoelectric coupling coefficient of the sample presents a symmetrical shape about the origin (0, 0); Similarly, in the process of changing the scanning field from -2kOe to 0 and then to 2kOe, Example 8 (Ba 1.6 Sr 1.4 Co 1.25 Cu 0.75 Fe 24 O 41 The dynamic magnetoelectric coupling coefficient of the sample ) also presents a symmetrical shape about the origin (0, 0); the difference is that when the scanning direction changes, Example 8 (Ba 1.6 Sr 1.4 Co 1.25 Cu 0.75 Fe 24 O 41 ) The direction of the magnetoelectric coupling coefficient of the sample is changed, so under the condition of reverse polarization electric field, the embodiment 8 (Ba 1.6 Sr 1.4 Co 1.25 Cu 0.75 Fe 24 O 41 ) Regulation of the magnetoelectric coupling coefficient of the sample.
[0133] In summary, Example 8 (Ba 1.6 Sr 1.4 Co 1.25 Cu 0.75 Fe 24 O 41 ) The magnetoelectric coupling coefficient of the sample changes with the scanning field. It can be found that under the same scanning field conditions, under different polarization electric field conditions, Example 8 (Ba 1.6 Sr 1.4 Co 1.25 Cu 0.75 Fe 24 O 41 )The directions of the magnetoelectric coupling coefficients of the samples are opposite.
[0134] Therefore, Example 8 (Ba 1.6 Sr 1.4 Co 1.25 Cu 0.75 Fe 24 O 41) The magnetoelectric coupling coefficient of the sample can be controlled by the direction of the external scanning field and the direction of the prepolarization electric field. It has potential application advantages in the field of non-volatile storage based on magnetoelectric coupling. 1.6 Sr 1.4 Co 1.25 Cu 0.75 Fe 24 O 41 ) The magnetoelectric coupling tolerance temperature of the sample can be seen that Example 8 (Ba 1.6 Sr 1.4 Co 1.25 Cu 0.75 Fe 24 O 41 )'s magnetoelectric coupling tolerance temperature fails to exceed room temperature, and does not have the magnetoelectric coupling performance under room temperature conditions. 1.6 Sr 1.4 Co 1.25 Cu 0.75 Fe 24 O 41 The dynamic magnetoelectric coupling coefficient of the sample under low temperature conditions reaches up to 7.2mV / cm Oe.
[0135] from Fig.11 It can be seen that Example 9 (Ba 1.8 Sr 1.2 Co 1.25 Cu 0.75 Fe 24 O 41 )It exhibits magnetoelectric coupling performance both at low temperatures and at room temperature and above.
[0136] Under the positive polarization electric field, in the process of sweeping the field from 2kOe to 0 and then to -2kOe, Example 9 (Ba 1.8 Sr 1.2 Co 1.25 Cu 0.75 Fe 24 O 41 ) The dynamic magnetoelectric coupling coefficient of the sample presents a symmetrical shape about the origin (0, 0); Similarly, in the process of changing the scanning field from -2kOe to 0 and then to 2kOe, Example 9 (Ba 1.8 Sr 1.2 Co 1.25 Cu 0.75 Fe 24 O 41 ) samples also present a symmetrical shape about the origin (0, 0); the difference is that when the scanning direction changes, Example 9 (Ba 1.8 Sr 1.2 Co1.25 Cu 0.75 Fe 24 O 41 ) The direction of the magnetoelectric coupling coefficient of the sample is changed, so by changing the direction of the scanning field, the embodiment 9 (Ba 1.8 Sr 1.2 Co 1.25 Cu 0.75 Fe 24 O 41 ) Regulation of the direction of the sample's magnetoelectric coupling coefficient.
[0137] Under the reverse polarization electric field condition, in the process of sweeping the field from 2kOe to 0 and then to -2kOe, Example 9 (Ba 1.8 Sr 1.2 Co 1.25 Cu 0.75 Fe 24 O 41 ) The dynamic magnetoelectric coupling coefficient of the sample presents a symmetrical shape about the origin (0, 0); Similarly, in the process of changing the scanning field from -2kOe to 0 and then to 2kOe, Example 9 (Ba 1.8 Sr 1.2 Co 1.25 Cu 0.75 Fe 24 O 41 ) samples also present a symmetrical shape about the origin (0, 0); the difference is that when the scanning direction changes, Example 9 (Ba 1.8 Sr 1.2 Co 1.25 Cu 0.75 Fe 24 O 41 ) The direction of the magnetoelectric coupling coefficient of the sample is changed, so under the condition of reverse polarization electric field, the embodiment 9 (Ba 1.8 Sr 1.2 Co 1.25 Cu 0.75 Fe 24 O 41 ) Regulation of the magnetoelectric coupling coefficient of the product.
[0138] In summary, Example 9 (Ba 1.8 Sr 1.2 Co 1.25 Cu 0.75 Fe 24 O 41 ) The magnetoelectric coupling coefficient of the sample changes with the scanning field. It can be found that under the same scanning field conditions, under different polarization electric field conditions, Example 9 (Ba 1.8 Sr1.2 Co 1.25 Cu 0.75 Fe 24 O 41 )The directions of the magnetoelectric coupling coefficients of the samples are opposite.
[0139] Therefore, Example 9 (Ba 1.8 Sr 1.2 Co 1.25 Cu 0.75 Fe 24 O 41 ) The magnetoelectric coupling coefficient of the sample can be controlled by the direction of the external scanning field and the direction of the prepolarization electric field. It has potential application advantages in the field of non-volatile storage based on magnetoelectric coupling. 1.8 Sr 1.2 Co 1.25 Cu 0.75 Fe 24 O 41 ) The magnetoelectric coupling tolerance temperature of the sample can be seen that Example 9 (Ba 1.8 Sr 1.2 Co 1.25 Cu 0.75 Fe 24 O 41 )'s magnetoelectric coupling tolerance temperature fails to exceed room temperature, and does not have the magnetoelectric coupling performance under room temperature conditions. 1.8 Sr 1.2 Co 1.25 Cu 0.75 Fe 24 O 41 )The dynamic magnetoelectric coupling coefficient of the sample under low temperature conditions reaches a maximum of 4.45mV / cm Oe.
[0140] In summary, by regulating Ba / Sr in Z-type hexagonal ferrite, it is possible to not only achieve the regulation of the sample's magnetoelectric coupling coefficient, but also effectively regulate the sample's magnetoelectric coupling tolerance temperature. In the samples of this study, the Ba-doped components in the 0.2-1.8 component range all have dynamic magnetoelectric coupling performance. In particular, the tolerance temperature of the dynamic magnetoelectric coupling performance of the samples with Ba-doped components in the 0.2-1 range exceeds room temperature, and the dynamic magnetoelectric coupling performance tolerance temperature reaches up to 350K, which has potential application advantages in the field of magnetoelectric coupling. The dynamic magnetoelectric coupling coefficient of the implementation sample under low temperature conditions is shown in Table 1.
[0141] Table 1 Dynamic magnetoelectric coupling performance of Z-type hexagonal ferrite
[0142]
[0143]
[0144] Through the test of the dynamic magnetoelectric coupling performance of the implementation sample, it was found that when the ratio of the introduced Ba and Sr was 1:1, the implementation sample had a maximum dynamic magnetoelectric coupling coefficient of 9.13mV / cm Oe, which has potential advantages in the field of magnetoelectric coupling. When the content of the introduced Ba is in the range of 0.2 to 1.8, the sample has excellent magnetoelectric coupling performance under low temperature conditions, and the direction of the dynamic magnetoelectric coupling performance of the implementation sample can be regulated by the direction of the prepolarization electric field. When the content of the introduced Ba is in the range of 0.2 to 1, the magnetoelectric coupling tolerance temperature of the sample implementation sample exceeds room temperature, which has potential advantages in the practical application of magnetoelectric coupling.
[0145] The above describes the specific embodiments of the present invention. It should be noted that the present invention is not limited to the above specific embodiments, and those skilled in the art can make various modifications or variations within the scope of the claims, which does not affect the essential content of the present invention.
Claims
1. A Z-type hexagonal ferrite magnetoelectric coupling ceramic material, characterized in that: Its chemical formula is Ba x Sr 3- x Co 1.25 Cu 0.75 Fe 24 O 41 ; Wherein, x=0~3.
2. The magnetoelectric coupling ceramic material according to claim 1, characterized in that: x=0.2-1.8。 3. The magnetoelectric coupling ceramic material according to claim 1, characterized in that: x=0.2~1.0。 4. The magnetoelectric coupling ceramic material according to claim 1, characterized in that: x=0.2、0.6、1.0。 5. The magnetoelectric coupling ceramic material according to claim 3, characterized in that: The magnetoelectric coupling performance of the magnetoelectric coupling ceramic material can withstand a temperature of 300K to 350K.
6. The method for preparing the magnetoelectric coupling ceramic material according to any one of claims 1 to 4, characterized in that: The following steps are involved:
1. Weigh BaCO3, SrCO3, Co3O4, CuO and Fe2O3 according to the chemical formula, wet-mill them together, and then dry-mill them; 2. Pre-sintering: firstly, heating to 1000℃ at a rate of 5℃ / min and maintaining for 10h, then cooling to 500℃ at a rate of 5℃ / min, and then naturally cooling to room temperature to obtain pre-sintered powder; 3. Wet ball milling the calcined powder, drying it, and then dry ball milling it; 4. Then, polyvinyl alcohol solution is added dropwise, ground evenly, sieved, and tableted to obtain a block body; 5. Debinding the block blank; 6. Then sintering in an oxygen atmosphere: heating to 1000°C at a rate of 5°C / min, then heating to 1100°C-1140°C at a rate of 2°C / min and maintaining for 10 hours, then cooling to 1000°C at a rate of 2°C / min, then cooling to 500°C at a rate of 5°C / min, and naturally cooling to room temperature to obtain Z-type hexagonal ferrite; 7. Place the Z-type hexagonal ferrite obtained in step 6 into a tube furnace. In an oxygen atmosphere, heat the tube furnace to 950°C at a rate of 5°C / min and keep it warm for 14 days, then cool it to 500°C at a rate of 5°C / min, and then naturally cool it to room temperature to obtain a Z-type hexagonal ferrite magnetoelectric coupling ceramic material.
7. The method according to claim 5, characterized in that: In step 1, wet ball milling is performed using 95% (volume) ethanol as a ball milling medium at a speed of 400 r / min for 12 h; drying is performed at 90° C. for 8 h; and dry ball milling is performed at a speed of 500 r / min for 10 min.
8. The method according to claim 5, characterized in that: In step 4, the mass concentration of the polyvinyl alcohol solution is 5%; the material is added in a ratio of 10 drops of polyvinyl alcohol solution to 5 g of solid.
9. The method according to claim 5, characterized in that: In step 4, the tablet is pressed at a pressure of 6 MPa.
10. The method according to claim 5, characterized in that: In step 5, the debinding is carried out at 500°C for 10 hours.
Citation Information
Patent Citations
High-saturation magnetization Z-type hexagonal ferrite powder and preparation method thereof
CN112851325A
Z-type hexagonal ferrite magnetoelectric coupling ceramic material and preparation method thereof
CN115677338A
Y-type hexagonal ferrite magnetoelectric coupling ceramic material and preparation method thereof
CN118084472A
Components and preparing process of VHF plate sensor material
CN1397961A
